2021
DOI: 10.1016/j.pnpbp.2020.110159
|View full text |Cite
|
Sign up to set email alerts
|

The psychiatric and neuropsychiatric repercussions associated with severe infections of COVID-19 and other coronaviruses

Abstract: Introduction It is known that viral infections are epidemiologically prevalent and some of them are harmful to the central nervous system (CNS) due to the development of neuropsychiatric syndromes which affect the cognitive, affective, behavioral and perceptual domains. Objective To carry out a comprehensive analysis of the psychiatric and neuropsychiatric repercussions of COVID-19 based on epidemiological, pathophysiological and clinical foundations observed in previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 39 publications
1
46
0
9
Order By: Relevance
“…In some studies, it has been reported that the initial symptoms of COVID-19 may be neuropsychiatric in nature. Patients may present delirium, cerebrovascular complications, encephalopathy, anosmia, and neuromuscular disorders [37,38]. On the other hand, patients with a previous psychiatric diagnosis may be more vulnerable to COVID-19 and may be at higher risk for negative consequences.…”
Section: The Effects Of Covid-19 On Mental Healthmentioning
confidence: 99%
“…In some studies, it has been reported that the initial symptoms of COVID-19 may be neuropsychiatric in nature. Patients may present delirium, cerebrovascular complications, encephalopathy, anosmia, and neuromuscular disorders [37,38]. On the other hand, patients with a previous psychiatric diagnosis may be more vulnerable to COVID-19 and may be at higher risk for negative consequences.…”
Section: The Effects Of Covid-19 On Mental Healthmentioning
confidence: 99%
“…Eine Metaanalyse (8 Studien, 11 054 Fälle) ergab eine Prävalenz von 75 % Geruchsstörungen und 81 % Geschmacksstörungen [30]. Oft werden daher GGS auch als Screening-Symptom angesehen [31,32]. Warum die Angaben zu GGS so stark variieren, ist unklar.…”
Section: Neurologische Manifestationenunclassified
“…Hypoaktive Formen scheinen dabei fast so häufig wie hyperaktive aufzutreten und prognostisch quoad vitam ungünstiger zu sein [46]. Für die Genese des Delirs besonders bedeutsam wird die durch die Störung der Lungenfunktion bedingte Hypoxie gehalten [21], jedoch sind auch Fälle von Delirien ohne Beeinträchtigung der Lungenfunktion beschrieben [31]. Bei vorbestehender Demenz kann das Delir schon früh im Erkrankungsverlauf auftreten [43,47,48], was mit einer besonders schlechten Prognose einhergeht [48].…”
Section: Organische Störungen Kognitive Störungenunclassified
“…Over the course of the pandemic, the general population has been subjected to stressors derived from the social and economic impacts of the virus 28,44 . It is, for this reason, di cult to separate the actual contribution of the biological factors highlighted in this article from other environmental factors.…”
Section: Component 6: Depression and Anxiety Related Variablesmentioning
confidence: 99%